SEPARAÇÃO DE MATERIAIS RECICLÁVEIS: PANORAMA NO BRASIL E INCENTIVOS À PRÁTICA - Neves, Ana Cláudia Ribeiro Rossi; Castro, Luiz Otávio de Almeida (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706631 One of the challenges generated by the Brazilian Solid Waste Policy, which entered intoforce in Brazil in August 2010, is the adherence to the selective collection of municipal waste. Datafrom government institutions and scientific research have shown that millions of tons of municipalsolid waste per year still have improper destination in the country and only 14% of cities operatestructured selective collection of recyclable material programs. Even in cities that rely on selectivewaste collection programs, the amount of recyclable materials despised is still great and the lowparticipation of the population in the separation of materials contributes to this scenario. Thepresent study aims to portray the situation of separation and collection of recyclable materials inBrazil and present the results of studies that identified factors that motivate the practices ofseparation and the barriers in several countries.